Composite dietary antioxidant index of antioxidant vitamins and sarcopenia risk: insights from the UK biobank and NHANES cohorts - HuiMin Liu; YuDi Xu; QingSheng Li; LingFei Yang; Xuan Yang; KaiXin Wang; Zhe Gong; Qiang Zhang; YanJie Jia (Nutrition & Metabolism)
Abstract Background The composite dietary antioxidant index (CDAI), reflecting total dietary intake of antioxidant vitamins, may indicate overall antioxidant capacity. This study examined its association with the risk of probable sarcopenia, defined by handgrip strength, in older adults. Methods Participants aged over 60 from the UK Biobank (N = 22,921) and National Health and Nutrition Evaluation Surveys (NHANES) 2011–2014 (N = 2,641) cohorts were categorized into probable sarcopenia and non-probable sarcopenia groups. Multivariable logistic regression models assessed the associations between CDAI (both continuous and quartile) and its components (vitamin A, vitamin C, vitamin E, and carotene) with probable sarcopenia risk in cohorts, with sex subgroup and sensitivity analyses to validate results. Results The median (interquartile range) of CDAI was -0.39 (-1.88, 1.45) in the UK Biobank and -0.57 (-1.60, 0.84) in NHANES, respectively. A higher CDAI was significantly associated with a lower risk of probable sarcopenia in both cohorts. Specifically, each one-unit increase in CDAI was associated with a 2% decrease in the odds of probable sarcopenia in the UK Biobank (OR = 0.98, 95% CI = 0.97–0.998, p = 0.027) and a 13.5% decrease in NHANES (OR = 0.865, 95% CI = 0.75–0.997, p = 0.045), after full adjustment under the Sarcopenia Definition and Outcomes Consortium (SDOC) criteria. In quartile analyses, the risk of probable sarcopenia tended to decrease across higher CDAI quartiles, although the dose–response trend was not strictly linear. In the UK Biobank, multivariable-adjusted odds ratios (95% CIs) across increasing CDAI quartiles were: Q1 (reference), Q2 = 0.87 (0.78–0.97), Q3 = 0.91 (0.81–1.01), and Q4 = 0.86 (0.77–0.96). In NHANES, the trend was more pronounced: Q1 (reference), Q2 = 0.47 (0.24–0.94), Q3 = 0.39 (0.19–0.82), and Q4 = 0.46 (0.22–0.95). Additionally, higher dietary intake of carotene, one of the key antioxidant components, was independently associated with a lower risk of probable sarcopenia in both cohorts. Subgroup analyses indicated an inverse association between CDAI and probable sarcopenia risk in females across both cohorts, whereas no significant association was observed in males. Sensitivity analyses confirmed the robustness of these findings. Conclusions Increased dietary intake of antioxidant vitamins may reduce the risk of probable sarcopenia in older adults, emphasizing the need for targeted prevention strategies. Further research on underlying mechanisms and sex differences is warranted.